Performance of Universities based on Research Output - Koto, J; Syukri, M; Sofyan Arief, Dodi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
Performance of universities based on research ranking has become a trend to gauge the credibility and quality of the university. One of the parameters used to assess university ratings is the result of research in the form of papers, patents, copyrights. Therefore, universities in the world compete to publish research results in the form of journals or conferences and others. This paper discusses on performance of universities based on research output. The results of research index in developed countries shows that there is not much change from year to year, it may be said that it almost reaches a saturation point. On the other side of the earth, the increase in research results in ASEAN countries is still high, reaching 70-80 percent. More impressive, universities in Indonesia have tried very enthusiastically in the study as the percentage increase was 500%.